HUBUNGAN SIKAP DAN MOTIVASI KADER LAYANAN KOMPREHENSIF BERKESINAMBUNGAN (LKB) TERHADAP UPAYA PENCEGAHAN HIV/AIDS - Hafiz, Rasfani; Dewi, Yulia Irvani; Karim, Darwin (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2018)
Human Immunodeficiensy Virus (HIV) is a virus that attacks white blood cells in the human imun system. This virus develops in the body until the condition of the body becomes Acquired Immuno Deficiency Syndrome (AIDS). HIV/AIDS is still being a problem not only in Indonesia but also in the word. There are many program control of HIV/AIDS in Indonesia which is conducted by the goverment one of item is Continuous Comprehensive Services (LKB). LKB involves all of comunity which act as a LKB cadres. The purpose of this research is to know the relationship between attitude and motivation of comprehensive and sustinable service (LKB) cadre in HIV/AIDS prevention efforts. The method of this research is descriptive correlation with cross sectional approach. The study was conducted on 100 LKB cadres at Tenayan Raya Public Health Center, Rumbai Public Health Center and Senapelan Public Health Center using cluster sampling technique. Measuring tool used in the form of questionnaire and has been tested the validity and reliability. The analysis used is univariate analysis and bivariate analysis using Chi Square test. The results showed that there was a correlation between attitudes toward HIV/AIDS prevention efforts (p value = 0.018) and there was a correlation between motivation for HIV/AIDS prevention (p value = 0,017). It is suggested to the Public Health Center in order to increase the empowerment of LKB cadres so that the prevention effort of HIV/AIDS becomes more optimal.Keyword: HIV/AIDS, Kader, LKB, Upaya Pencegahan